Effects of green tea supplementation on inflammation markers, antioxidant status and blood pressure in NaCl-induced hypertensive rat model - Szulińska, Monika (Food Nutr Res, 2017)
Background: Recent studies indicate the important role of chronic inflammation and oxidative stress in the pathogenesis of hypertension. Green tea, due to the high content of catechins, shows high antioxidant activity. Objective: To determine the effect of supplementation with green tea extract on the blood pressure, on the concentration of selected parameters of inflammation and antioxidant status in the model of high-sodium-diet induced hypertension. Design: The study lasted 42 days. The experimental population consisted of 30 rats. The rats were divided into three groups. The rats in the control group were fed a standard diet with 35 g of NaCl per kg of diet, in the second group hypertensive rats were fed a standard diet with NaCl (35 g/kg diet) and with an extract of green tea (2 g/kg diet). The third group consisted of hypertensive rats fed a standard diet with NaCl (35 g/kg diet), and 4 g of green tea extract/kg diet. Results: Supplementation with green tea had no effect on body mass of rats on a high-sodium diet. At the end of the experiment systolic blood pressures in SH2 and SH4 groups were significantly lower than in the control group SK. The SH4 group was characterized by a significantly lower diastolic blood pressure value and concentration of TNF-α in comparison to the SK group. The rats from both SH2 and SH4 groups were characterized by higher total antioxidant status values compared to the control group. Discussion: The mechanism of the beneficial effects of green tea on blood pressure is not clear, but it is believed that it is related to its omnidirectional properties. Conclusions: Supplementation of green tea has a beneficial effect on blood pressure, markers of inflammation and antioxidant status in an experimental model of hypertension.